As percepções e os significados para os estagiários de educação física em relação à indisciplina na escola - dos Santos, Ivan Luis [UNESP]; Rodrigues, Heitor de Andrade [UNESP]; Fuzzi, Fabio Tomio [UNESP]; de Oliveira, Ricardo Simoes [UNESP]; de Oliveira, Mateus Kerr [UNESP]; Peluqui, Daniela Fernanda [UNESP]; Darido, Suraya Cristina [UNESP] (Universidade Federal do Rio Grande do Sul (UFRGS), Escola de Educação Física, 2008)
This research investigated the perceptions and the meanings for the trainees of Physical Education regarding the indiscipline in the school. The methodology used was from qualitative nature, having as participants 16 students of a public course of Physical Education. The indiscipline was pointed by the trainees while a present problem in their practices and connected to different difficulties. Therefore, as methodological procedures more mentioned, appeared the blackmail, the agreements and the dialogue, being the school institution, outstanding while informative of the rules, of the rights and of the students' duties.
The perceptions and the meanings for the trainees of Physical Education regarding the indiscipline in the school
Keywords: Behavior; Physical Education; Education, primary and secondary